2007
DOI: 10.1523/jneurosci.0006-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination, Astrogliosis, and Accumulation of Ubiquitinated Proteins, Hallmarks of CNS Disease inhsf1-Deficient Mice

Abstract: The heat shock transcription factors (Hsfs) are responsible for the heat shock response, an evolutionarily conserved process for clearance of damaged and aggregated proteins. In organisms such as Caenorhabditis elegans, which contain a single Hsf, reduction in the level of Hsf is associated with the appearance of age-related phenotypes and increased accumulation of protein aggregates. Mammalian cells express three hsfs (hsf1, hsf2, hsf4) and their role in CNS homeostasis remains unclear. In this study, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 47 publications
3
68
0
Order By: Relevance
“…Santos and colleagues noted that their HSF1 KO brains had enlarged ventricles and astrogliosis, particularly in white matter regions (30), while Homma and colleagues also identified diminished myelination in HSF1 KO mice and motor deficiencies (16). Thus, we conducted detailed neuropathological analysis of the HSF1 KO mice from our breeding colony, which is maintained on a mixed 129SV ϫ BALB/c ϫ C57BL/6 background, to determine whether these phenotypes were present.…”
Section: Characterization Of Neurological Parameters In Uninoculated mentioning
confidence: 96%
See 2 more Smart Citations
“…Santos and colleagues noted that their HSF1 KO brains had enlarged ventricles and astrogliosis, particularly in white matter regions (30), while Homma and colleagues also identified diminished myelination in HSF1 KO mice and motor deficiencies (16). Thus, we conducted detailed neuropathological analysis of the HSF1 KO mice from our breeding colony, which is maintained on a mixed 129SV ϫ BALB/c ϫ C57BL/6 background, to determine whether these phenotypes were present.…”
Section: Characterization Of Neurological Parameters In Uninoculated mentioning
confidence: 96%
“…It was also reported that HSF1 KO mice have abnormalities in their brains (16,30). Santos and colleagues noted that their HSF1 KO brains had enlarged ventricles and astrogliosis, particularly in white matter regions (30), while Homma and colleagues also identified diminished myelination in HSF1 KO mice and motor deficiencies (16).…”
Section: Characterization Of Neurological Parameters In Uninoculated mentioning
confidence: 98%
See 1 more Smart Citation
“…It would be interesting to determine whether reintroduction of gankyrin in Hsf2 À/À iMEF could restore the level of p53, knowing that it was already shown that gankyrin overexpression accelerates the degradation of p53 in various cell models, including MEF (Higashitsuji et al, 2005). Mivechi's group described a mechanism linking HSF1 deficiency and p53 stabilization (Homma et al, 2007;Jin et al, 2009). Our study confirms a role for HSF1 in the regulation of p53, with a slight stabilization of this protein in pulse-chase experiment compared with WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HSF1 is reported to be required for extraembryonic development, postnatal growth and fertility of the female in the HSF1-KO mice (47). Homma et al (48) observed hallmarks of central nervous system disease, such as demyelination, astrogliosis and accumulation of ubiquitinated proteins in HSF1-deficient mice. Furthermore, previous studies with HSF1 KO animals have shown that HSF1 is involved in the development and maintenance of several organs, such as the heart (49), trachea (50), nose (50) and placenta (47).…”
Section: Function Of Hsf1mentioning
confidence: 99%